CHRONIC OBSTRUCTIVE LUNG DISEASES (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Several lung diseases are characterized by impaired lung function, impaired airway permeability, and difficulty in exhalation. Among these lung diseases, chronic bronchitis, especially bronchiolitis, pulmonary emphysema, bronchial asthma, bronchiectasis have a special place and cause very specific anatomical changes. In this article, chronic obstructive pulmonary disease information about diseases.